Alternative lengthening of telomeres is the major telomere maintenance mechanism in astrocytoma with isocitrate dehydrogenase 1 mutation - Ventura Ferreira, Mónica Sofia; Sørensen, Mia Dahl; Pusch, Stefan; Beier, Dagmar; Bouillon, Anne-Sophie; Kristensen, Bjarne Winther; Brümmendorf, Tim Henrik; Beier, Christoph-Patrick; Beier, Fabian (Journal of neuro-oncology, 2020)
Isocitrate dehydrogenase 1 (IDH1) mutations are associated with improved survival in gliomas. Depending on the IDH1 status, TERT promoter mutations affect prognosis. IDH1 mutations are associated with alpha-thalassemia/mental retardation syndrome X-linked (ATRX) mutations and alternative lengthening of telomeres (ALT), suggesting an interaction between IDH1 and telomeres. However, little is known how IDH1 mutations affect telomere maintenance.
Gesehen am 14.04.2020